Public Accounting vs Private Accounting: Pengaruh Personal Branding terhadap Pilihan Karir Mahasiswa Akuntansi di Kota Padang - Rania Isra Athalla; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2024)
This study means to decide the amount of impact personal branding has on career choices of accounting students in picking a profession as a public accountant or private accountant. This study utilizes Holland's career choice theory. The population of this study were S1 accounting students in Padang City and information assortment was done utilizing a survey that was conveyed straightforwardly and through g form to accounting students at 6 colleges in Padang City. Hypothesis testing utilizing logistic regression analysis. The outcomes showed that 33.5% of the personal branding variable could impact the career choice variable of accounting students while the rest was affected by different factors.